2022
DOI: 10.3390/catal12060578
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic and DFT Modeling Studies on Suzuki–Miyaura Reactions of 4,5-Dibromo-2-methylpyridazin-3(2H)-one with Ferrocene Boronates, Accompanied by Hydrodebromination and a Novel Bridge-Forming Annulation In Vitro Cytotoxic Activity of the Ferrocenyl–Pyridazinone Products

Abstract: This paper presented the efficiency of different Pd-based catalytic systems in a series of SM reactions of 4,5-dibromo-2-methylpyridazin-3(2H)-one with ferroceneboronic acid, ferrocene-1,1′-diboronoc acid, and its bis-pinacol ester. In addition to the disubstituted product, these transformations afford substantial amounts of isomeric 4- and 5-ferrocenyl-2-methylpyridazin-3(2H)-ones, and a unique asymmetric bi-pyridazinone-bridged ferrocenophane with a screwed molecular architecture. The reactions of phenylboro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…It is of importance that due to its stability, super-aromaticity, elevated membrane-penetrating ability, and implication in substituent-dependent, thus finetuneable, ROS-generating single electron transfer (SET) events, organoferrocene fragments became the most widespread structural motifs in the emerging group of organometallics displaying anticancer activity triggered by versatile mechanisms of actions [24][25][26][27][28][29][30][31][32][33][34]. It has also been demonstrated that replacing an aromatic nucleus of certain organic compounds for a ferrocene unit can lead to products with antiproliferative activity that is absent or less manifested in the parent molecule [35][36][37][38].…”
Section: Figurementioning
confidence: 99%
“…It is of importance that due to its stability, super-aromaticity, elevated membrane-penetrating ability, and implication in substituent-dependent, thus finetuneable, ROS-generating single electron transfer (SET) events, organoferrocene fragments became the most widespread structural motifs in the emerging group of organometallics displaying anticancer activity triggered by versatile mechanisms of actions [24][25][26][27][28][29][30][31][32][33][34]. It has also been demonstrated that replacing an aromatic nucleus of certain organic compounds for a ferrocene unit can lead to products with antiproliferative activity that is absent or less manifested in the parent molecule [35][36][37][38].…”
Section: Figurementioning
confidence: 99%